The Aggregate Consequences of Tax Evasion - Alessandro Di Nola; Georgi Kocharkov; Almuth Scholl; Anna-Mariia Tkhir (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
There is a sizeable overall tax gap in the U.S., albeit tax noncompliance differs sharply across income types. While only small percentages of wages and salaries are underreported, the estimated misreporting rate of self-employment business income is substantial. This paper studies how tax evasion in the self-employment sector affects aggregate outcomes and inequality. To this end, we develop a dynamic general equilibrium model with incomplete markets in which heterogeneous agents choose between being a worker and being self-employed. Self-employed agents may hide a share of their business income but are confronted with the probability of being detected by the tax authority. Our model replicates important quantitative features of U.S. data, in particular, the misreporting rate, wealth inequality, and the firm size distribution. Our quantitative findings suggest that tax evasion induces self-employed businesses to stay small. In the aggregate, tax evasion increases the size but decreases the productivity of the self-employment sector. Moreover, it increases aggregate savings and reduces wealth inequality. We show that tax revenues follow a Laffer curve in the size of the tax evasion penalty.
Keywords: H24; H25; H26; C63; E62; E65; 330; Tax evasion; Self-Employment; Wealth inequality; Tax policy.